Role Play Game-Based Learning Multimedia for Elementary School Students - I Made Kartika; I Made Sila; Dewa Ayu Made Manu Okta Priantini; I Wayan Suastra; Ida Bagus Putu Arnyana (Jurnal Pendidikan dan Pengajaran, 2023)
Along with the development of science and technology, learning media has now developed by utilizing the flexibility of computers to solve learning problems. The problem behind this research is the lack of learning media for students in science subjects so that learning outcomes are less than optimal. This study aims to develop learning media in the form of multimedia based on role play games. This research is a research and development (research and development). The subjects of the research trial were grade IV students. The data collection instrument used was an evaluation sheet (questionnaire). Data analysis used descriptive qualitative and quantitative descriptive analysis. The results of the evaluation of the Role Play Game (RPG) Based Learning Multimedia product were carried out based on six aspects, namely: in terms of the learning design aspect with an achievement level percentage of 87.60% worthy; in terms of the aspect of individual trials, with a percentage of the achievement rate of 94.65%, the rating is very feasible; small group trials, with a percentage of achievement level of 94.65% predicate very feasible; and in terms of the aspect of field trials with a percentage achievement level of 95.00% predicate very feasible. Thus the product in the form of Role Play Game (RPG) Based Learning Multimedia has a good level of validity and is suitable for use in the learning process in science subjects.